2014
DOI: 10.1002/ese3.52
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and comparison analysis for application of PV panels in three villages

Abstract: In recent years, research about the application and optimization of PV panels has grown rapidly. Especially for stand-alone solar systems there have been some problems related to first stages of design and application. Finding the optimum slope of PV panels in order to maximize the absorbed solar radiation is considered as one of the major obstacles. Although in Malaysia there have been some research works about finding of optimal tilt angle, however, this research work aims to start investigation about slope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Figure 1(c) illustrated that the angle of the solar collector box is 0° to the cabinet. The tilt angle of the solar collector with a range of 0° to 15° is suitable to receive the maximum solar radiation in any location in Malaysia [11]. There are no wheels, blower or fan in this design.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1(c) illustrated that the angle of the solar collector box is 0° to the cabinet. The tilt angle of the solar collector with a range of 0° to 15° is suitable to receive the maximum solar radiation in any location in Malaysia [11]. There are no wheels, blower or fan in this design.…”
Section: Methodsmentioning
confidence: 99%
“…The greater the angle, the lower the solar intensity, which is why the R s parameter is less intense in the morning and evening than at noon [89,101]. Furthermore, the annual net Rs is higher at the equator than at the northern and southern poles [28,102]. Also, as a hemisphere is tilted away from the sun, the R s value decreases [68,96,103,104].…”
Section: Light Intensitymentioning
confidence: 99%
“…These two systems are intended to offer a direct current or alternating current source for use with the utility grid, an independent storage system, or other electrical/electronic equipment [77,93,119,120]. Even though much of the photovoltaic system demand can be matched with aggressive building-integrated PV (BIPV) and rooftop PV [79,87,95,102], both systems cannot provide all the energy necessary, especially for regions with high population densities compared to land-based solar farms [8,95]. A solar farm is designed to generate enough energy [37] to power thousands of homes and business [9,121].…”
Section: Alteration and Modification Of Solar Photovoltaicmentioning
confidence: 99%
“…Meanwhile, the annual optimum tilt angle is close to Bangi's latitude, which is 1.4 • facing due south, while the optimum angles for seasonal south-and north-facing surfaces were found to be 14.4 • ± 5 • and 14.8 • ± 5 • , respectively. Lastly, a study conducted by [41] intended to evaluate the fixed optimum tilt angle of PV panels at three rural villages, namely Kampung Opar (Sarawak, Malaysia), Kampung Labi (Beaufort, Sabah, Malaysia), and Kampung Orang Asli Kemendol (Selangor, Malaysia). The Liu and Jordan model is applied in this study, and the result has shown that the optimal tilt angle in these three locations is under 5 • .…”
Section: Solar Modelsmentioning
confidence: 99%